Forced Resettlements: From Impacts to Opportunities – The Case of Moatize Mine (Mozambique) - Pedro, Joana (2015)
The combination of an increasing population and the expansion of needs imposed by consumer society has triggered an increase in the number of projects such as roads, dams and mines. Many of these projects lead to the displacement of populations that are voicelessly taken to other locations through forced resettlements, thus becoming “development refugees”. In region of Tete, Mozambique, the discovery of one of the largest world’s coal reserves has led to a mass resettlement process that has affected and will continue to affect thousands of people in the next years. The World Bank states that it should be ensured that resettled populations have their living conditions improved. The current paper analyses, trough quality of life indicators, the resettlement made by the mining company Vale in Moatize, Tete province, between 2006 and 2011. Although it is still very early to tell whether the quality of life will improve or deteriorate in the future, certain results can already be identified in the present. On the one hand, improvements have been registered in some basic living conditions such as education, health or access to water and energy. On the other hand, the level of cultural identity of the population and their survival strategies seem to have deteriorated – which is reflected today in the impoverishment of some families and in the claim shared by part of the population they feel like guests in their own houses.